The effect of career compromise on nurses' turnover intention: the mediating role of job satisfaction - Zhanghao Xie; Zhongqing Chen; Waner Wang; Jiangfeng Pu; Gege Li; Jiehao Zhuang; Xuanhao Fan; Ziyi Xiong; Hanxi Chen; Yuemei Liang; Peng Xu; Huigen Huang (BMC, 2024)
Abstract Aim We aimed to examine the relationships among nurses' career compromise, job satisfaction, and turnover intention and the mediating role of job satisfaction in the relationship between career compromise and turnover intention. Background Nurses are prone to career compromise when there is a discrepancy between the reality of their job and their personal career expectations due to personal or family factors. High levels of career compromise may have a significant impact on turnover intentions through low job satisfaction, thereby affecting the stability of the nursing workforce. There is a paucity of research on the impact of nurses' career compromise on turnover intentions. Method This was a cross-sectional research design of nurses in hospitals in Guangdong Province using a convenience sampling method. The Career Compromise Scale (CCS), Job Satisfaction Scale (JSS), and Turnover Intention Scale (TIS) were used. The obtained data were analyzed through descriptive statistics, Spearman's correlation coefficient, and the mediating effect of perceived organizational support was tested through the PROCESS macro mediation model in SPSS. Results Data from 821 nurses who met the inclusion criteria were analyzed. The total score of nurses' turnover intention was 14.68 ± 4.32. Spearman's correlation analysis showed that career compromise was negatively correlated with job satisfaction (r = -0.594, p < 0.01), job satisfaction was negatively correlated with turnover intention (r = -0.471, p < 0.01), and career compromise was positively correlated with turnover intention (r = 0.544, p < 0.01). The mediating effect of job satisfaction on the relationship between career compromise and turnover intention has been demonstrated. The mediating effect is significant, with a value of 0.056, representing 25.71% of the total effect. Conclusions The turnover intention of nurses in Guangdong Province is high. Job satisfaction mediated the relationship between career compromise and turnover intention. This study further enriches JD-R theory and COR theory and provides new perspectives for nurse managers to develop intervention strategies to stabilize the nursing workforce and reduce turnover.